Enhancing mathematical connection skills: Interactive “Sikoma” media powered by smart apps creator - Winda Widyaningsih; T. Trimurtini; Teguh Supriyanto (Universitas Muhammadiyah Malang, 2024)
Mathematical connection skills are needed in various ways. Innovations in learning mathematics such as media innovation improve students’ abilities. This development research develops Sikoma (Aplikasi Koneksi Matematis) interactive learning media using the ADDIE model which is expected to be valid, practical, and effective. The research subjects in the small-scale trial were 6 students of Elementary school of Tancep 2 grade IV, while the large-scale trial was 21 students of Elementary school of Tancep 1 grade IV. Based on the results of the validation value obtained that Sikoma learning media reached an average score of 93,1% with a very feasible category. The results of students’ responses obtained an average result of 98% so Sikoma interactive learning media can be practical. A paired sampel T-test result obtained that Sikoma interactive learning media can improve mathematical connection skills and using the N-Gain method gets an average score of 0,67 which is included in the moderate category. It is concluded that the Sikoma interactive learning media has proven be valid, practical, and effective to improving mathematical connection skills. It is hoped that this research can make a positive contribution in the form of interactive learning media in the field of education especially in mathematics education to improve students’ mathematical connection abilities.